PROSEDUR DAN TEKNIK PEMBUATAN PERATURAN DESA DI DESA PENFUI TIMUR KECAMATAN KUPANG TENGAH KABUPATEN KUPANG - Bunga, Gerald Aldytia; Tuan, Yohanes; Asnawi, Norani; Helan, Yohanes Golod. Tuba; Tupen, Rafael Rape; Lamataro, Cyrilius Wilton Taran (Jurnal Abdi Insani, 2024)
Although Law Number 6 of 2014 concerning Villages gives authority to the Village Head and Village Consultative Body to be able to form Village Regulations, in fact no Village Regulations have been produced. The objectives of this activity include: a) providing knowledge about aspects that need to be regulated in Village Regulations; b) providing knowledge about the process of forming Village Regulations; c) providing knowledge and skills to find and determine problems that can be regulated in a Village Regulation; and d) providing knowledge about the systematics, sentences and legal language in Village Regulations. This activity was carried out using the survey method, briefing and interactive question and answer/dialogue which were divided into two stages, namely the preparation stage and the implementation stage. This activity involved 40 participants consisting of the Village Head, Village Apparatus, Village Consultative Body (BPD), and the community. The training activity on Village Regulation drafting techniques in Penfui Timur Village is a solution for solving the problems faced. Through this activity, it is hoped that there will be an increase in knowledge and skills in drafting Village Regulations in Penfui Timur Village.